Parallel Homologous Search With Hirschberg Algorithm: A Hybrid MPI-Pthreads Solution. - Abdul Rashid, Nur'Aini; Abdullah, Rosni; Hj. Talib, Abdullah Zawawi (2007)
In this paper, we apply two different parallel programming model, the message passing model using Message Passing Interface (MPI) and the multithreaded model using Pthreads, to-protein sequence homologous search. The protein sequence homologous search uses Hirschberg algorithm for the pair-wise sequence alignment.